Effects of melatonin and gonadal androgens on cell proliferation in the pituitary of viscachas (Lagostomus maximus maximus) - Rosales, Gabriela Judith (2016)
Objectives: Melatonin and androgens are involved in the regulation of cell proliferation. However, effects of these hormones on pituitary pars distalis (PD) of male viscachas is not fully understood. In the present study, we analysed melatonin and gonadal androgens’ effects on proliferating cell nuclear antigen (PCNA) expression. Materials and methods: Pituitary glands from foetuses, immature individuals, prepubertal individuals and adult viscachas during their reproductive cycle, after melatonin administration and after castration, were used. PCNA-ir cells were detected by immunocytochemistry and morphometrically quantified using image analysis. Results: Total percentage of PCNA-ir cells varied seasonally in the adult pituitary, with maximum values during the reproductive period and minima during gonadal regression periods. Percentages of PCNA-ir cells increased after melatonin administration, whereas it decreased after castration. Caudal end and ventral regions were the PD zones which were most affected by seasonal variations and castration. PCNA expression was highest in foetal pituitary from midpregnancy. Numbers of PCNA-ir cells decreased during sexual maturity. Conclusions: Our results demonstrate the effect of gonadal androgens on cell proliferation during the reproductive period and sexual maturity of these animals. Exogenous melatonin increased PD cell proliferation in adults. Thus, these hormones seem to be involved in different mechanisms that regulate cell renewal of PD in this seasonally breeding rodent.